Pengaruh Penambahan Konsentrasi (NH2)2CO Terhadap Karakteristik TiO2 dan Aktifitas Fotokatalitiknya Dalam Mendegradasi Methylene Blue - Novera Elsi Mudia; Rahadian Zainul; Deski Beri; Syamsi Aini (Departemen Kimia FMIPA UNP, 2022)
Titanium dioxide (TiO2) is a semiconductor material that is often applied as a photocatalyst. TiO2 has a band gap of 3.20 eV which is less effective when used in visible light. Nitrogen dopants are dopants that have high effectiveness to improve the performance of TiO2 in the visible light region. This study aims to determine the effect of adding nitrogen dopant concentration on the characteristics of TiO2 and its photocatalytic activity in degrading methylene blue. The photocatalytic activity of TiO2-N was tested with 10 ppm methylene blue under sunlight for 1 hour. The addition of dopants to the TiO2 matrix has an effect on the band gap and photocatalytic activity of TiO2